Correlation between performance and feeding behavior of feedlot lambs fed without roughage diet - Cardoso, Elves de Souza; Santana Junior, Hermógenes Almeida de; Oliveira, Aracele Prates de; Ferreira, Antônio Hosmylton Carvalho de; Oliveira, Zeliana Fernandes de; Freitas, Tiago Brandão (Acta Scientiarum. Animal Sciences, 2017)
The objective was to evaluate the correlation between performance and feeding behavior of feedlot castrated Santa Inês lambs fed without roughage diet, weighing 20 ± 1,8 kg and four months of age (± 0,34). A completely randomized design was adopted. Correlations were obtained by Pearson’s linear correlation analysis and the t test, and processed on SAS software (version 9.2). The variables number of rumination chews per cud, number of cuds ruminated per day, speed of each chew, and number of rumination cuds per day were positively correlated with the variation in body weight (p < 0.05). For number of cuds ruminated per day, a positive correlation was found with the variations in body weight. Initial and final body weights were positively correlated with the feed and rumination efficiencies of the lambs feeding behavior and with the time per period spent feeding and performing other activities. Feeding time had a positive correlation with variation in body weight per day and the relative variation in body weight. Rumination was positively correlated with performance variables. The correlations show that there is influence between eating behavior and performance.